Collective displacements in a molecular crystal polymorphic transformation - Zahn, Dirk; Anwar, Jamshed (RSC Advances, 2013)
A long-standing question is whether concerted molecular displacements can occur during first-order phase transformations in molecular crystals. We have investigated the molecular level mechanism of the temperature-induced extgreekb i̊ghtarrow extgreeka phase transition in the molecular crystal DL-norleucine using molecular dynamics (MD) simulations. The simulations have employed the transition path sampling MD approach coupled with quenching to ascertain the mechanism of transformation close to the coexistence temperature, which is more representative of laboratory conditions than conventional brute-force MD that involves excessive superheating to induce the transformation. The study reveals that on length scales below 10 nm the extgreekb ̊htarrow extgreeka transformation in DL-norleucine crystals occurs by a concerted layer displacement mechanism. This finding is significant since collective structural transitions could be the mechanisms of choice in molecular crystals with hydrogen-bonded layers or chains, which are considered to be particularly amenable to control and have the potential to form the basis for molecular machines that transform heat into mechanical work.
EAM Import::2019-03-13